Revitalization of Islamic Values of Kompangan Traditional Music at the Jambi Cultural Arts Institution in Seberang City in Jambi Province (Catharsis, 2022)
One of the traditional arts in Jambi Province is Kompangan music. Kompangan, in traditional ceremonies in Jambi, is often displayed to welcome guests of honor, traditional leaders, and religious events and is also often used for wedding processions. Therefore, the presence of Jambi Malay kompangan and hadrah arts, the hallmark of the Jambi people, is always synonymous with Islam. The presence of kompangan in the ceremony is very important so that kompangan is known, loved, and cherished even by children. In addition, the art of kompangan music has its charm so that it is easily remembered and accepted by the public. This study describes the revitalization process and the Islamic values of Kompangan traditional music at the Jambi Cultural Arts Institution in Seberang City, Jambi Province. The type of research used is descriptive qualitative—data collection techniques with observation, interviews, and documentation. The research results showed that the revitalization process went through six stages: the discovery stage of new views, the communication stage, the organizational stage, the adaptation stage, the transformation stage, and the routine stage. The Islamic values of Kompangan traditional music are individual moral, family, social, national, religious and Islamic character values, which are contained in music, musical instruments, procedures, and clothing.